2006
DOI: 10.5688/aj700107
|View full text |Cite
|
Sign up to set email alerts
|

Medication Management in Primary and Secondary Schools

Abstract: Objectives. To identify whether and how pharmacy faculty members are addressing the issue of medication management in primary or secondary schools in their teaching, research, and service activities, and to ascertain the extent to which they think the issue is an important one. Methods. Four hundred ninety-nine faculty members completed a questionnaire inquiring about the research, teaching, and service activities in which they participated that related to medication management in schools. Results. Only 33 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These results are consistent with the few other studies suggesting that medication administration is a significant issue facing schools, families, and health care providers that requires systematic collaboration to address. Reutzel, Patel, and Myers (2001) reviewed 95% of the literature identified through a thorough search process and concluded that a set of core medication management guidelines are identifiable. More importantly, they found that pharmacists and school nurses must work effectively together to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the few other studies suggesting that medication administration is a significant issue facing schools, families, and health care providers that requires systematic collaboration to address. Reutzel, Patel, and Myers (2001) reviewed 95% of the literature identified through a thorough search process and concluded that a set of core medication management guidelines are identifiable. More importantly, they found that pharmacists and school nurses must work effectively together to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…19 Some schools have developed relationships between school nurses and pharmacists to enhance medication distribution and safety. 19,20 Such collaboration between school nurses and pharmacists have the potential to address pharmaceutical waste management and help determine when, how, and where unused and expired medications can be safely disposed. Nevertheless, school districts accumulate many unclaimed prescription and OTC medications.…”
mentioning
confidence: 99%
“…Medication use in primary and secondary schools encompasses a variety of steps including medication transfer from the parent to the school, storage at appropriate temperatures, proper administration to a student, and disposal of expired and leftover medications . Some schools have developed relationships between school nurses and pharmacists to enhance medication distribution and safety . Such collaboration between school nurses and pharmacists have the potential to address pharmaceutical waste management and help determine when, how, and where unused and expired medications can be safely disposed.…”
mentioning
confidence: 99%
“…1 Some schools struggle to balance the need for health care services for increasing numbers of children with special health care needs with the current resources available to provide those services. [2][3][4][5][6][7][8][9][10][11][12] The presence in schools of a full-time licensed registered school nurse is strongly endorsed. 13 Registered nurses (RNs) have the knowledge and skills required for the delivery of medication, the clinical knowledge of the student's health, and the responsibility to protect the health and safety of all students.…”
Section: Introductionmentioning
confidence: 99%